Peak oxygen uptake of healthy Iranian adolescents - Amra, Babak; Kelishadi, Roya; Golshan, Mohammad (Archives of Medical Science, 2009)
Introduction: Maximal oxygen uptake (VO2max) has an important place in the assessment of cardiopulmonary fitness. Currently there is insufficient normative data for Iranian adolescents. With this preliminary study, we aimed to set up the first normative data for our laboratory which may also serve as a basis for future large population-based studies in Iran. Material and methods: We assessed the peak oxygen consumption of 95 healthy Iranian adolescents, aged 13-17 years, and examined the cardiopulmonary responses to exercise test in relation to their age, sex and body size. Between June and September 2007, the level of aerobic capacity was evaluated by maximal oxygen consumption (VO2max), which was calculated using the exercise test on a bicycle ergometer. Results: During a four-month period, the cardiopulmonary exercise test was conducted on a population-based sample of 95 adolescents (44 boys and 51 girls). The mean age and body mass index were 15.59 ±1.85 years and 23.46 ±5.05 kg/m 2 , respectively. The VO2max of boys was significantly higher in boys than in girls (16.71 ±8.72/12.48 ±6.25 ml/kg/min respectively, p = 0.001). Conclusions: The current study presents normal data for a small representative sample of healthy Iranian adolescents. VO2max in our study was in the poor to average range when compared to the standard values of other populations. This information should prompt policy makers and medical educators to address this problem, and to consider promoting exercise and integrating physical fitness into the school curriculum.